2005
DOI: 10.1021/ma0501794
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Semicrystalline−Rubbery−Semicrystalline Triblock Copolymers

Abstract: Microstructure of and mechanical properties of a series of symmetric EPE (E = poly(ethylene-co-1-butene) and P = poly(ethylene-alt-propylene)) triblock copolymers with M n = 27−372 kg/mol have been investigated in the solid state. Microphase separation of EPE triblock copolymers originates from either (i) chemical incompatibility-induced microphase separation in the melt before crystallization at high overall molecular weights or (ii) crystallization-induced microphase separation from a homogeneous melt at low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
105
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(112 citation statements)
references
References 38 publications
7
105
0
Order By: Relevance
“…Monodisperse triblock copolymers form softer, yet denser hydrogels, with more uniform micelles, allowing for intermicellar slip under shear stress. This hypothesis is supported by the literature …”
Section: Resultssupporting
confidence: 81%
“…Monodisperse triblock copolymers form softer, yet denser hydrogels, with more uniform micelles, allowing for intermicellar slip under shear stress. This hypothesis is supported by the literature …”
Section: Resultssupporting
confidence: 81%
“…As shown in Figure , the polymer gave two different phase domains, that is, the hard segments (s‐1,2‐PBD) aggregated and acted as nodal points distributed in the polymer matrix homogeneously, whereas the phase corresponding to the soft segments (e‐PBD) surrounded the hard segment phase. The microdomain formation in semicrystalline block copolymer could result either from the incompatibility of two blocks or the crystallization of one or both blocks . Two major mechanisms might govern the assembly morphology of the stereoblock PBD.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] The number of available possible conformations reduces because the restricted geometries imposed on crystallizing polymer materials are on a nanometer scale, which is approximately the length of a polymer chain in coil form. [3][4][5][6][7][8][9][10][11][12][13][14][15][16] Therefore, the nanoscaled confinement size plays an important role in crystallization kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] The number of available possible conformations reduces because the restricted geometries imposed on crystallizing polymer materials are on a nanometer scale, which is approximately the length of a polymer chain in coil form. [3][4][5][6][7][8][9][10][11][12][13][14][15][16] Therefore, the nanoscaled confinement size plays an important role in crystallization kinetics. 9e, 16,17 Our previous work indicated that a distinct transformation of isothermal crystallization kinetics, from heterogeneous to homogeneous nucleation, occurred between two neighboring glassy lamellar layers when the confined size became less than 8 nm (equivalent to the size of forming a stable nucleus via heterogeneous nucleation), leading to an abrupt shift in crystallization to a lowtemperature region.…”
Section: Introductionmentioning
confidence: 99%